Case of Unrecognised of Maxillary Adenoid Cystic Carcinoma - Danica Vidović Juras; Ivana Škrinjar; Spomenka Manojlović; Igor Blivajs; Dalibor Franćeski; Luka Manojlović; Vanja Vučićević Boras (University of Zagreb. School of Dental Medicine, 2019)
Adenoid cystic carcinoma is a less commonly diagnosed cancer that may affect the major or minor salivary glands. We present a 70 year old male patient who was admitted to the Department of Oral Medicine, School of Dental Medicine in Zagreb, Croatia due to pain in the right maxilla. In this case we report a case of the patient with unilateral pain in the maxilla & eye which lead to the diagnosis of adenoid cystic cancer without any visible oral lesions.